Efficacy of fresh maca (Lepidium meyenii walp) in the sportsmen increment in physical performance at high altitude - Ronceros, Gerardo (2005)
Objective: To establish the effect of fresh maca (Lepidum meyenil walp) on the sportsmen physical performance at high altitude. Design: Comparative, prospective, and experimental study. Materials and Methods: Ten high altitude sportsmen constituted the sample. We first measured the maximum oxygen consumption under physical activity. Then they received 1500 mg of fresh maca daily during 60 days and a second evaluation was performed under similar conditions. The maximum oxygen intake and performance were determined and subjects were monitored for a 30 days period. Dosage of transaminases ALAT, ASAT, and serum creatinine were done during each evaluation. Results: In basal conditions the velocity average in the treadmill was 15,46 km/h and the maximum oxygen intake average was 52,32 mL/kg/min. In the second evaluation following the fresh maca consume the average of the maximum velocity raised to 16,89 km/h and the maximum oxygen intake was 57,75 mL/kg/min, which means a 10,3% increase in physical performance. In all cases, the ALAT, ASAT, and serum creatinine values were normal. Conclusions: Fresh maca revealed energizing properties that increase the sportsmen physical performance at high altitude.